2019
DOI: 10.1097/sla.0000000000003440
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Visceral Protection in Preventing Enteroatmospheric Fistulae During Open Abdomen Treatment in Patients With Secondary Peritonitis

Abstract: Objective:To evaluate the influence of a visceral protective layer (VPL) on the formation of enteroatmospheric fistulae (EAF) in open abdomen treatment (OAT) for peritonitis.Background:EAF formation is a severe complication of OAT. Despite the widespread use of OAT, there are no robust evidence-based recommendations for preventing EAF.Methods:A total of 120 peritonitis patients with secondary peritonitis as a result of a perforation of a hollow viscus or anastomotic insufficiency who had undergone OAT were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
(100 reference statements)
0
19
0
1
Order By: Relevance
“…There have been seven systematic reviews examining methods of TAC in the OA over the last 10 years[539,542,570,[573][574][575][576][577] and three RCTs[559,578,579]. The overall strength of the reported outcomes is low due to the small number and poor quality of comparative observational studies.Management of the OA requires a multidisciplinary approach, led jointly by the surgical and intensive care teams with input from a nutritional team, physiotherapists, complex wound and stoma nurses and guided by microbiology.Patients remain intubated following the creation of an OA after index laparotomy, primarily to facilitate repeated returns to…”
mentioning
confidence: 99%
“…There have been seven systematic reviews examining methods of TAC in the OA over the last 10 years[539,542,570,[573][574][575][576][577] and three RCTs[559,578,579]. The overall strength of the reported outcomes is low due to the small number and poor quality of comparative observational studies.Management of the OA requires a multidisciplinary approach, led jointly by the surgical and intensive care teams with input from a nutritional team, physiotherapists, complex wound and stoma nurses and guided by microbiology.Patients remain intubated following the creation of an OA after index laparotomy, primarily to facilitate repeated returns to…”
mentioning
confidence: 99%
“…Patients with the indication for OAT and in whom primary fascial closure is impossible during the abdominal surgery are treated with a commercially available OAT dressing kit (ABThera TM SensaTRAC TM Open Abdomen Dressing, KCI Medical/3M, Maplewood, MN, United States). To protect the viscera from serosal lesions and prevent enteroatmospheric fistulas, a visceral protective layer integrated into the abdominal vacuum foam is implanted (19). It is placed deep laterally in the paracolic spaces to prevent lateral adhesions.…”
Section: Description Of Surgical Techniquementioning
confidence: 99%
“…The main procedure-inherent risks in patients undergoing OAT are (1) the development of an entero-atmospheric fistula (EAF), (2) failure of primary fascial closure (PC) resulting in a planned ventral hernia (PVH), and (3) high rates of incisional hernias after PC. Recent studies have demonstrated that a structured approach including (a) the use of a visceral protection layer, (b) mesh-mediated fascial traction, and (c) negative pressure wound treatment reduces the above-mentioned complications significantly ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, The World Society of Emergency Surgery suggests early fascial closure as the key strategy for the management of open abdomen with a grade 1B recommendation ( 8 ). The recent literature also suggests that early closure should be achieved within 10 days ( 4 , 9 ). Thus, while hospital discharge with PVH after OAT becomes less frequent, the incidence of an incisional hernia after open abdomen treatment is high ( 6 ).…”
Section: Introductionmentioning
confidence: 99%